Sweat rate, salt loss, and fluid intake during an intense on-ice practice in elite Canadian male junior hockey players - Palmer, M. S.; Spriet, L. L. (Applied Physiology, Nutrition, and Metabolism, 2008)
Previous research in many sports suggests that losing ~1%-2% body mass through sweating impairs athletic performance. Elite-level hockey involves high-intensity bursts of skating, arena temperatures are >10 °C, and players wear protective equipment, all of which promote sweating. This study examined the pre-practice hydration, on-ice fluid intake, and sweat and sodium losses of 44 candidates for Canada`s junior men`s hockey team (mean ± SE age, 18.4 ± 0.1 y; height, 184.8 ± 0.9 cm; mass, 89.9 ± 1.1 kg). Players were studied in groups of 10-12 during 4 intense 1 h practices (13.9 °C, 66% relative humidity) on 1 day. Hydration status was estimated by measuring urine specific gravity (USG). Sweat rate was calculated from body mass changes and fluid intake. Sweat sodium concentration ([Na]) was analyzed in forehead sweat patch samples and used with sweat rate to estimate sodium loss. Over 50% of players began practice mildly hypohydrated (USG > 1.020). Sweat rate during practice was 1.8 ± 0.1 L/h and players replaced 58% (1.0 ± 0.1 L·h-1) of the sweat lost. Body mass loss averaged 0.8% ± 0.1%, but 1/3 of players lost more than 1%. Sweat [Na] was 54.2 ± 2.4 mmol/L and sodium loss averaged 2.26 ± 0.17 g during practice. Players drank only water during practice and replaced no sodium. In summary, elite junior hockey players incurred large sweat and sodium losses during an intense practice, but 2/3 of players drank enough to minimize body mass loss. However, 1/3 of players lost more than 1% body mass despite ready access to fluid and numerous drinking opportunities from the coaches.